Production of Starch Esters by Roasting Potato Starch with Unripe Apple Juice - Wioletta Drożdż; Małgorzata Kapelko-Żeberska; Tomasz Zięba; Artur Gryszkin; Ewa Tomaszewska-Ciosk; Urszula Sielczak (Applied Sciences)
Within the framework of this study, starch esters were produced from potato starch roasted with unripe apple juice concentrate. Starch roasting with an apple juice concentrate at temperatures of 70 °C, 80 °C, and 100 °C enabled the production of preparations with a low degree of substitution, whereas starch roasting at 120°C and 140 °C produced preparations with a high degree of substitution. The latter had a significant effect on the properties of the malates produced. The esters with a low degree of substitution featured higher solubility in water and swelling power, higher initial and end pasting temperatures, and higher viscosity compared to those with a low degree of substitution. An increasing substitution degree was accompanied by diminished susceptibility of the starch esters to the effects of amylolytic enzymes, which suggests the presence of resistant starch in the modified preparations. Production of starch esters with the use of a natural apple concentrate may offer a viable alternative to conventional chemical modifications applied in the food industry and an environmentally friendly method for producing modified starch preparations applicable in the manufacture of low-energy foods with potential health benefits.